Heat transfer evaluation of saturated pool boiling outside slender tube bundle in passive residual heat removal system of molten salt reactor. (May 2022) - Tao, Ding; Guang-liang, Yang; Kai-Lun, Chen; Guang-Ming, Fan; Zhao-Ming, Meng; Chang-Qi, Yan; Ke-fan, Zhang; Hong-Li, Chen
Highlights: The overall and local pool boiling heat transfer characteristics of slender tube bundles are studied. Ten prediction correlations of overall average heat transfer characteristic in saturated boiling were analyzed and compared. The special local boiling HTC and the local wall superheat distribution of the vertical tube bundle in this experiment were found, analyzed and explained.** Four prediction correlations of local pooling boiling heat transfer characteristic were compared and discussed. A new local boiling heat transfer model is proposed. Abstract: In order to study the operation feasibility and safety margin of the water-cooled passive residual heat removal system applied to 2 MW molten salt reactor (MSR), the heat transfer characteristics of some local components in the system were experimentally investigated thoroughly. In the later stage of system operation, the water in the tank will reach saturation. In this paper, the overall and local pool boiling heat transfer characteristics outside the tube bundle of condenser are studied. A special local boiling heat transfer coefficient (HTC) distribution is found and the formation mechanism is explained. The experimental results are compared with four empirical correlations for local boiling HTCs. The errors between the four correlations and their applicability to the experimental results are discussed. A new boiling heat transfer correlation is proposed based on the experimental data.